Pengaruh Intellectual Capital, Leverage dan Profitabilitas Terhadap Nilai Perusahaan (Pada Perusahaan yang Terdaftar Pada Indeks LQ45 2019-2021) - Ari Gunawan, Muhammad; Utami Lestari, Tri (Jurnal Ilmiah Akuntansi Peradaban, 2023)
This study aims to determine the effect of Intellectual Capital, Leverage and Profitability on Firm Value in companies listed on the LQ45 index for 2019-2021. This study uses a quantitative method based on descriptive research objectives. The data collection method in this study was unobtrusive observation or non-reactive method. The results of the study show that Intellectual Capital, Leverage and Profitability have a simultaneous effect on firm value of 59.25%. Each of the Intellectual Capital, Leverage and Profitability variables has a partial positive effect on company value in companies listed in the LQ45 index for 2019-2021. Keyword: Intellectual Capital, Leverage, Profitability and Corporate Value